Hypoglossal Nerve Paralysis Caused by Diffuse Idiopathic Skeletal Hyperostosis - Christina Fanous; Radwan Mashina; Ammar Jum'ah; Marwan Mashina; Edwin Avallone (Annals of Internal Medicine: Clinical Cases)
Diffuse idiopathic skeletal hyperostosis (DISH) is a rare disease characterized by bony overgrowth of the spine. If severe enough, it can lead to dysphagia from many different mechanisms. These most commonly include mechanical obstruction, inflammation, or vocal cord paralysis. In our patient case, DISH caused paralysis of the hypoglossal nerve, which contributed to his dysphagia. Paralysis of the hypoglossal nerve as a result of DISH has not yet been reported in the literature.